Service Learning of Nutrition and Dietetics Students in the Community: A Phenomenological Study - Idaosos, Merlina G.; Aclan, Eunice M.; Oasan, Ruchelle (Journal of International Scholars Conference - ALLIED HEALTH, 2016)
The qualitative study described the shared experiences of Nutrition and Dietetics (ND) senior students of the Adventist University of the Philippines in their two-month service learning in the community. Specifically, this phenomenological study answered the following research questions: (1) What have Nutrition and Dietetics students experienced in their community exposure? (2) What are the issues and challenges the participants experienced in their community service learning? (3) How has the community exposure of the participants impacted their professional outlook? Focus group interview (FGI) was used to collect data from six participants selected through purposive sampling. The FGI was conducted by the researchers themselves in a conducive place for 53 minutes. The audio-recorded interview data were transcribed, analyzed, and interpreted. The findings revealed that the community service learning of the ND students did not only focus on applying the knowledge and skills on their specialization but also integration of faith and learning as they shared God’s love and other aspects of their learning at AUP including health and hygiene, science, livelihood, and values. The participants found it challenging how to plan meals according to the available local resources and to design programs that suit the needs of their target groups and hold them long for lectures. The participants’ actual community experience also taught them how to be flexible in handling various situations; leave their comfort zones to serve the poor and needy; interact with and respect different people of various ages, education level, and economic status; and extend their services to the community not just to comply with university requirements but to show love to the less privileged people. The participants’ service learning experience also made them realize their crucial role as ND specialists to promote proper nutrition and good health to the community people.